An alternative to the straddle-arm technique for a conscious infant who is choking: Towards a more universal skill - Ada Chan; Adam Gesicki (International Journal of First Aid Education)
Problem The practice of straddling the infant’s legs on the rescuer’s upper arm, during the delivery of back blows and chest thrusts for the relief of foreign body obstruction (choking) in infants is not physically possible for many rescuers. We aimed to identify a more effective set of practices for holding an infant during the delivery of back blows and chest thrusts. Methods Using a participatory ergonomic research, study participants trialed alternative techniques in a structured and co-creative discovery process alongside a researcher. This was done with the aid of a custom-developed manikin, weighted and sized to the 50th percentile of a 9–11-month-old. Participant feedback was solicited quantitatively and qualitatively. Results & Conclusion Of the 40 initially enrolled, 37 participants completed the study protocol. We concluded that one technique appeared to be most amenable to research participants. This technique involves keeping the infant on the same side of the participant and rolling the baby to allow for the administration of back blows and chest thrusts. This paper also presents a thematic summary of the various considerations that became apparent throughout the work with participants. This one technique is put forward as a recommendation for how the skill should be taught, by default, within learning environments.